SIMULASI DAMPAK PERUBAHAN IKLIM TERHADAP KEMAMPUAN TANAH MENYIMPAN AIR TERSEDIA DAN POTENSI PRODUKSI PADA TANAMAN KAKAO DI KABUPATEN MALANG - Anis Nur Afifah; Sugeng Prijono (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2022)
Cocoa is one of the mainstay commodities of Malang Region, which is sensitive to climate change. This research aimed to simulate climate change and its impact on water availability for cocoa plants in Donomulyo, Dampit, and Kromengan of Malang Regency using a simulated water balance method with climate change scenarios based on predictions from Indonesia Meteorological, Climatological, and Geophysical Agency (BMKG) and Intergovernmental Panel on Climate Change (IPCC). The climate change scenario consisted of an increase in air temperature of 0.5,  0.7, and 1°C, combined with changes in rainfall -5, -10, and -20%. Climate change impacted the air temperature increase at the earth’s surface followed by rainfall pattern changing, thus affecting the agricultural sector related to water needed increase and water availability decreased for plants. The results showed that along with the increase in temperature and decrease in rainfall, the water demand increased by 1.08-2.31%. The water availability in the soil decreased, followed by an increase in production reduction. The reduction in cocoa production occurred in each scenario with the highest percentage in scenario C9 (ΔT1⸰C, ΔH-20%). Production reduction results from not meeting the water needs of cocoa plants because it has a value greater than the ability to store water in the soil that occurs in several phases of cocoa plant growth, especially during the dry month period.